Curriculum Management at the Pusat Kegiatan Anak of Sahabat Anak Foundation - Manullang, Lumi Sartika; Suryadi, Suryadi; Karnati, Neti (Journal of Nonformal Education, 2022)
Curriculum management is a cooperative, comprehensive, systemic, and systematic curriculum management system to achieve curriculum goals. The purpose of this study is to find out the curriculum management at Children Activity Center Sahabat Anak Foundation in Jakarta including the planning, organization, implementation, and evaluation of the curriculum. This study uses qualitative descriptive approach and research data obtained through interviews with the director of the organization, operational director, head of the education division, and teachers. The results show that curriculum planning is well managed even though there is no standard curriculum available. The curriculum at the centre is designed based on children's needs, age, and learning outcomes where parents, children, teachers, and management involved in designing and determining the activities. Curriculum organization and implementation are carried out by referring to the scheduled events that have been planned. It is found that there is versatility in meeting objectives when implementing the curriculum. The educational team carries out curriculum assessment and monitoring, and teachers are invited to report per visit and clarify activities implemented with children in conjunction with the predetermined curriculum. This novelty of this research is the contribution to the development of education management towards street children specifically and education in general